Anti-inflammation of spirocyclopiperazinium salt compound LXM-10 targeting α7 nAChR and M4 mAChR and inhibiting JAK2/STAT3 pathway in rats. - Weiwei Zhang; Qi Sun; Xiaoli Gao; Yimin Jiang; Runtao Li; Jia Ye (PLoS ONE, 2013)
The present study aims to investigate the therapeutic effects of LXM-10 by intragastric administration in both acute and chronic inflammatory models, and to explore the underlying molecular mechanisms. The results showed that LXM-10 produced significant anti-inflammatory effects on carrageenan induced paw edema and complete Freund's adjuvant (CFA) induced arthritis, in which LXM-10 inhibited paw swelling in a dose- and time-dependent manner. ELISA analysis showed the production of pro-inflammatory cytokines including TNF-α and IL-6 was decreased by LXM-10. Western blot analysis showed that LXM-10 significantly reduced phosphorylation of Janus kinase 2 (JAK2) and further blunted phosphorylation of signal transducer and activator of transcription-3 (STAT3). The effects that LXM-10 had shown were attenuated by methyllycaconitine citrate (an α7 nicotinic acetylcholine receptor antagonist) or tropicamide (an M4 muscarinic acetylcholine receptor antagonist) in vivo. In conclusion, the studies showed that intragastric administration of LXM-10 exerted significant anti-inflammation effects in acute and chronic models, which may be attribute to the activation of α7 nicotinic acetylcholine receptor and M4 muscarinic acetylcholine receptor, thereby inhibiting the JAK2/STAT3 signal pathway, and ultimately reducing the production of pro-inflammatory cytokines of TNF-α and IL-6.